A Note on Women's Courtesy Titles in Chinese. (1st October 2016) - Chen, Lindsey N. H.
Abstract : This study examines the use of women's courtesy titles in contemporary Taiwanese society. In particular, 245 native Mandarin speakers were asked to complete a survey that was modeled on the one used by Donna Lillian. The results show that age is an influential factor in the selection of courtesy titles for women of different marital status. They also confirm Lillian's observation that a woman's occupational status may outweigh her marital status. The study lends insight into the uses of courtesy titles across cultures and briefly suggests areas worth exploring in future research.